1995
DOI: 10.1002/jnr.490400104
|View full text |Cite
|
Sign up to set email alerts
|

Time course of ciliary neurotrophic factor mRNA expression is coincident with the presence of protoplasmic astrocytes in traumatized rat striatum

Abstract: Adrenal grafting for Parkinson's disease has led to modest functional improvement despite poor graft survival. One explanation is a neurotrophic response within the traumatized striatum. This study was undertaken to investigate the time course of the astrocytic response in vivo and in vitro, and the expression of ciliary neurotrophic factor (CNTF) mRNA following striatal injury. Unilateral stereotaxic biopsy of the rat striatum was performed and gelatin sponge (gel-foam) was immediately placed into the biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 35 publications
1
32
0
2
Order By: Relevance
“…But it has not been determined which ligand is most relevant during normal development, nor have studies elucidated which ligands are important for the expansion of NSPs after injury (which we probably need not emphasize is likely a more complex process than maintenance). Many studies on injuries to the adult brain have shown that CNTF is dramatically increased (Ip et al, 1993,Asada et al, 1995,Herx et al, 2000,Albrecht et al, 2003. Based on these data we hypothesized that CNTF would increase after neonatal H/I whereupon it would signal through its cognate receptor to effect expansion of the NSPs in the SVZ.…”
Section: Discussionmentioning
confidence: 94%
“…But it has not been determined which ligand is most relevant during normal development, nor have studies elucidated which ligands are important for the expansion of NSPs after injury (which we probably need not emphasize is likely a more complex process than maintenance). Many studies on injuries to the adult brain have shown that CNTF is dramatically increased (Ip et al, 1993,Asada et al, 1995,Herx et al, 2000,Albrecht et al, 2003. Based on these data we hypothesized that CNTF would increase after neonatal H/I whereupon it would signal through its cognate receptor to effect expansion of the NSPs in the SVZ.…”
Section: Discussionmentioning
confidence: 94%
“…Neurotrophic factors are produced around the locus of CNS lesions, and although earlier studies did not identify the source of these factors (NietoSampedro et al, 1982(NietoSampedro et al, , 1983Needels et al, 1986;Ernfors et al, 1989;Ishikawa et al, 1991;Lindvall et al, 1994), more recent studies have documented the upregulation of nerve growth factor (NGF) (Bakhit et al, 1991;Altar et al, 1992;Oderfeld-Nowak et al, 1992;Arendt et al, 1995), ciliary neurotrophic factor (Ip et al, 1993;Asada et al, 1995;Wen et al, 1995), basic fibroblast growth factor (Finklestein et al, 1988;Frautschy et al, 1991;GomezPinilla et al, 1995;Wen et al, 1995), and insulin-like growth factor-1 (Komoly et al, 1992) in reactive astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of both CNTF and its receptor, the CNTFR␣, are induced following injury to the central nervous system (CNS; Ip et al, 1993;Rudge et al, 1994;Asada et al, 1995;Oyesiku et al, 1997). Moreover, CNTF protein accumulates in wound cavities (Nieto-Sampedro et al, 1982;Asada et al, 1996) and is elevated in the cerebral spinal fluid (CSF) of patients with acute multiple sclerosis (MS ;Massaro, 1998).…”
Section: Introductionmentioning
confidence: 99%